Disseminated Melioidosis with multiorgan failure in a Diabetic and Chronic Kidney Disease patient with a sad outcome - Saha, Lima; Azad, Md Abul Kalam; Aftab, Kazi Ali; Monira, Shirajum; Murshed, Khaled Mahbub; Ikhtaire, Shapur (Bangladesh Journal of Medicine, 2024)
Melioidosis is caused by Burkholderiapseudomallei. It has recently gained importance as emerging pathogen in Bangladesh. It causes various clinical manifestations like pneumonia, septicemia, arthritis, subcutaneous and deep seated abscess associated with high morbidity and mortality. Few cases have been reported mainly from southeast asia. Such wide range of presentation & mimicry with other infection leads to misdiagnosis or underdiagnosis. This case report outlines a 58-year-old male’s progression from melioidosis to septicemia with multiple organ failure leading to death. Initial presentation was fever, bilateral leg swelling including right knee joint with subcutaneous abscess over both leg and foot. This case emphasizes the need of timely identification & tailored intervention to prevent devastating complication & mortality. Bangladesh J Medicine 2024; Vol. 35, No. 2, Supplementation: 177